Determinants of the human capital development and the national economy: economic and mathematical modeling of the relationship - Koibichuk, Vitaliia; Drozd, Serhii (Herald of Economics, 2024)
Introduction. The relationship between public health and the national economy is complex and multifaceted. On the one hand, people’s health affects their productivity, efficiency, and creativity, affecting the country’s economic performance. On the other hand, financial conditions in the country affect the availability and quality of medical services, food, housing, and other factors that determine the multifaceted essence of people’s health.The purpose of the study. The research aims to develop integral health indicators as a crucial component of human capital and the national economy. It also checks four hypotheses: hypotheses H1 and H2 are aimed at checking the significance of relationships between integral indicators; hypothesis H3 – verification of the influence of health indicators on the integral indicator of the national economy; hypothesis H4 is devoted to the question of whether indicators of the national economy influence the integrated indicator of health.Research methods. The research is based on the methods of data search, analysis and normalization, and multivariate statistical analysis. Integral indicators of health and the national economy were developed using the technique of principal component analysis in Statistica 12 software using additive convolution. This technique made it possible to determine weight values for each component included in the integral indicators. To assess the significance of relationships in the obtained paired regressions for integral indicators and in models describing the influence of health indicators on the integral indicator of the national economy, the impact of the indicators of the national economy on the integral indicator of health, statistical criteria of Student, Fisher, values were used coefficients of determination, confidence intervals, and significance levels using Stata 18 software.Results. During the study, a database of nineteen macro indicators for 38 countries related to health care and the national economy was collected in different scales and units of measurement. The data are normalized for the subsequent algorithm to test the four research hypotheses. Integral indicators are calculated with the help of additive convolution, considering the values of weighting coefficients for stimulating factors and destimulating factors of human capital and the national economy. According to the proposed hypotheses, four regression analyses were performed. It was found that when the integral index of the national economy changes by one unit, the integral index of health will change by 0.9305. In the opposite situation, the indicator of the national economy will change by 0.3214 when the integral indicator of health changes by its unit of measurement. The analysis of the influence of the components of the national economy on the integral indicator of health revealed a statistically significant positive influence of three indicators: the index of freedom of doing business, freedom of trade, and gross national income per capita. Analysis of the impact of the healthcare sector’s components on the national economy’s integral indicator did not reveal any statistically significant indicator.Prospects are aimed at the further development of scientific and methodological support for modeling the influence of human capital as an essential component of the health economy on the efficiency of the national economy and the implementation of practical measures to increase the level of human capital, which depends on the values of the indicators of the national economy of a particular country. The obtained values of integral indicators for the countries of the study firstly provide information about their level of human capital and national economy and, secondly, characterize their position in the field of economy and health. The significance of the impact of the indicators of the national economy on the integral indicator of human capital will allow the governing bodies of the respective countries to realize the tendencies towards changes, the development of further policies, and the implemented reforms in the fields of the national economy and health.